Keanekaragaman dan Potensi Tumbuhan Obat di Kampus 1 Universitas Islam Negeri Syarif Hidayatullah Jakarta - Muliyah, Evi; Fauzia, Hanna Diva; Azzahra, Kanisya Lativa; Yusniati, Euis (Universitas Medan Area, 2024)
This study explores the diversity and potential of medicinal plants at Campus 1 of Syarif Hidayatullah State Islamic University Jakarta. Using a qualitative descriptive method with an exploratory approach, plant samples were identified across six faculties on Campus 1. The results revealed 16 medicinal plant species from 14 families, with the most common species being lemongrass (Cymbopogon citratus). These plants have a wide range of uses, such as traditional remedies for pain, fever, and digestive disorders. The Shannon-Wiener diversity index for medicinal plants at Campus 1 of UIN Syarif Hidayatullah Jakarta falls into the moderate category (H’ = 2.193), indicating a moderate level of species diversity. The potential of these medicinal plants is highly relevant for research, education, and the development of natural product-based applications. Additionally, these plants serve as valuable learning tools for students in the fields of conservation and ethnobotany.